Molecular characterization of Fusarium spp. Isolates by using RAPD technique - Kakde, Rajendra B; Chavan, Ashok M (Journal of Ecobiotechnology, 2012)
Genetic diversity of ten Fusarium spp. isolates was studied by using RAPD technique. As Fusarium species were commonly occurred on all five oilseeds in almost all varieties especially showing abnormalities. Out of seven primers used three primers viz., OPAD-4, OPAD-7 and OPAD-18 gave amplification and produced twenty seven bands. The diversity index in dendrogram clearly indicate the distinct features which gives clear idea about the relation between Fusarium species isolates and seed content.Â 